Peningkatan Kemampuan Menulis Teks Eksplanasi Menggunakan Media Pembelajaran Gambar Fenomena Alam Siswa Kelas VIII SMP Nasional Banau Kota Ternate - Darlisa Muhamad; Adriani Adriani; Susrina Hud (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Ability to Write Explnatory Text Using Learning Media Pictures of Natural Phenomena for Grade VIII Students of Banau National Middle School, Ternate City. This study aims to describe and see the extent to which the ability to write explanatory texts is increased by using the learning media of natural phenomena pictures for class VIII students of Banau National Junior High School, Ternate City. This type of research is classroom action research (CAR) with data analysis techniques used, namely quantitative description techniques.. Based on the results obtained from this study that writing explanatory texts using pictures of natural phenomena as learning media can improve student learning outcomes in class VIII of Banau National Junior High School, Ternate City. This can be seen in the results of the first cycle test of 20 students who were declared to have completed learning only 3 students or 15.0% of students who completed the average score obtained was 67.25%. After doing the test in the second cycle, there was an increase with the average score obtained by 86.50% with the number of students who completed 20 students or 100%, because all students met the minimum completeness criteria (KKM) for Indonesian language subjects set at the Banau National Junior High School. The city of Ternate is 73. So it can be said that there was an increase from cycle I to cycle II by using pictures of natural phenomena for class VIII students at the Banau National Junior High School, Ternate City